PENINGKATAN EKONOMI BURUH PEMANEN SAWIT MELALUI PEMANFAATAN LIMBAH PELEPAH SAWIT MENJADI INOVASI PRODUK KERAJINAN - Indah Rahmawati (Universitas Pahlawan Tuanku Tambusai, 2025)
This Community Service Activity is one of the Efforts to improve the Economy of Palm Oil Harvesting Workers' Families by utilizing palm oil frond waste into an innovation of artistic craft products that have selling power and are expected to be additional income for participants. This activity aims to provide insight, skills, and other craft products by mothers of Palm Oil Harvesting Workers' wives, PKK and farmer groups through the Utilization of Palm Oil Frond Waste in Merbau Village, Bunut District, Pelalawan Regency; increase Innovation in palm oil frond waste management products that have selling and artistic value; improve the economy of mothers of Palm Oil Harvesting Workers' wives, PKK and farmer groups; and to mitigate land fires during the dry season caused by dried palm oil frond waste and supported by peat soil conditions. The approach used in this activity is to implement the Asset-Based Community Development (ABCD) approach. From the results of this Community Service activity, it was found that participants gained insight, skills, craft products and made a very significant contribution in efforts to improve the economy and income of participants' families by utilizing local resources in the form of oil palm fronds that can be found in the participants' residential environment. This activity in the initial stage succeeded in increasing the awareness and understanding of the participants of the creative economy and making them aware that local resources are around their homes that may be neglected because they do not know that they can be processed and have artistic value and are marketable. With this increase in understanding, it can motivate participants to be able to actively participate in training and can be applied and sustainable in the future, cooperation carried out with important figures and regional institutions in the form of Village Unit Cooperatives (KUD), Family Empowerment and Welfare (PKK) which synergize and collaborate in improving the economy and increasing the family income of participants in this community service activity.